Continous Infusion of Remifentanil Plus Ketamine Compared with Continous Remifentanil for Pain Relief in Labour - Anooshe Khajehdehi; Ashraf Moini; Bita Eslami; Nasrin Faridi Tazeh-Kand (Medical Journal of The Islamic Republic of Iran, 2011)
Abstract Background and objective: Pain relief during labour is an important determinant of a women’s birth experience. There are numerous pain relief techniques which can be used either with or without pain medication. The aim of our study was to compare the effect of remifentanil alone and its effect in pain relief while using with ketamine during labour. Methods: After obtaining informed consent and approval of hospital ethics committee, 40 women with gestational age between 38 and 42 weeks gestation in early labour were recruited for this study. They were randomly allocated into two groups: group RK (20 cases) received 25 μg remifentanil as a starting dose and continuous infusion of 0.06 μg/kg/min remifentanil plus 0.5 mg/kg/h ketamine for 4 hours via pump and group R (20 cases) received 25 μg remifentanil as a starting dose and continous infusion of 0.06 μg/kg/min remifentanil. Results: The baseline of pain scores were similar in both groups (5.75 ± 2.51 vs 7 ± 2.45, p= 0.12) but after 30 minutes to 120 minutes the VAS scores were significantly higher in R group (p< 0.001). The rate of patients who were satisfied (excellent and very good) in RK was 80% but in R group was 45% (p = 0.03). Nausea and vomiting were significantly higher in R group (p<0.05). Conclusion: The remifentanil plus ketamine produced better pain relief during labour with continous monitoring than continous remifentanil with no adverse effects for mothers and infants.